Multi-perspective analysis of skin microbiota in elderly eczema patients - Dake Dong; Qianjie Wu; Zijun Wang; Pengfei Xu; Tianqing Zhu; Ting Yang; Zhenghua Gu; Liang Zhang; Zitao Guo (PLoS ONE, 2025)
Eczema is a common inflammatory skin disease in elderly people. It not only causes physical damage to elderly people but also seriously affects their mental health. The skin microbiota plays a vital role in the development of skin disease. However, relatively few studies have investigated the characteristics of the skin microbiota in elderly eczema patients. In this study, the differences in the composition of the skin microbiota between lesion sites and healthy sites, between exposed sites and unexposed sites, and between elderly and younger eczema sites were analyzed, aiming to characterize the skin microbiota in elderly eczema patients from multiple perspectives and provide a basis for clinical diagnosis and treatment. The results indicated that the species richness of elderly eczema patients was greater than that of younger eczema patients. There was no significant difference between groups at the phylum level. At the genus level, the abundance of Staphylococcus significantly increased in the lesion sites of the elderly group. Compared with the younger eczema group, the elderly eczema group had greater abundances of Paracoccus, Deinococcus_B, Kaistella, Escherichia_710834, and Chryseobacterium_796703. These findings indicated that more attention should be given to the roles of Kaistella and Streptococcus in elderly eczema patients because Kaistella was the only genus among the 20 most abundant genera that was closely related to the EASI scores. Moreover, correlation analysis suggested that many genera had a positive relationship with Streptococcus. The results provide basic microbiological data for physicians treating elderly patients with eczema.